Psoriasis Comorbidities in Childhood - Nikolay N. Murashkin; Larisa S. Kruglova; Iuliia A. Kovalenko; Eduard T. Ambarchian; Roman V. Epishev; Alexander I. Materikin; Leonid A. Opryatin; Roman A. Ivanov; Daria S. Kukoleva; Daria G. Kuptsova; Marina Yu. Pomazanova; Ya. V. Kozyr ("Paediatrician" Publishers LLC, 2020)
Psoriasis is multifactorial systemic disease characterized by excessive hyperkeratosis due to impaired keratinocytes proliferation and differentiation. This disease often manifests in childhood and it is usually associated with the development of comorbid conditions some of which are combined by the term «psoriatic march» (obesity, metabolic syndrome, etc.). The course of psoriasis and related comorbidities in children has several specific features that determine topicality of studying all the aspects of clinical diagnosis and prevention in childhood. The article summarizes recent ideas on the prevalence, pathogenesis features and early diagnosis of comorbid diseases in children with psoriasis.